2020
DOI: 10.1016/j.eplepsyres.2020.106395
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis in mice treated with vigabatrin identifies dysregulation of genes associated with retinal signaling circuitry

Abstract: Vigabatrin (VGB; γ-vinyl-GABA) is an antiepileptic drug that elevates CNS GABA via irreversible inactivation of the GABA catabolic enzyme GABA-transaminase. VGB's clinical utility, however, can be curtailed by peripheral visual field constriction (pVFC) and thinning of the retinal nerve layer fiber (RNFL). Earlier studies from our laboratory revealed disruptions of autophagy by VGB. Here, we tested the hypothesis that VGB administration to animals would reveal alterations of gene expression in VGB-treated reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…We then compared the gene-based testing results with previously published gene-expression analysis. Walters et al identified 26 ocular function genes, that showed evidence of differential expression in mice exposed to VGB, compared to the controls ( Walters et al, 2020 ). We examined these 26 genes in our analyses to see if there was an enrichment of gene-based signal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then compared the gene-based testing results with previously published gene-expression analysis. Walters et al identified 26 ocular function genes, that showed evidence of differential expression in mice exposed to VGB, compared to the controls ( Walters et al, 2020 ). We examined these 26 genes in our analyses to see if there was an enrichment of gene-based signal.…”
Section: Resultsmentioning
confidence: 99%
“…We cross referenced results of our gene-based testing with 26 genes with ocular function that were previously shown to be differentially expressed in mice exposed to VGB, compared to the controls ( Walters et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%